Verbal Responses toward Insults in the Celebrity Read Mean Tweets Segment - Muflihatunnisa, Muflihatunnisa (Indonesian Journal of English Language Studies (IJELS), 2023)
Receiving insults virtually is one of the drawbacks of living with cutting-edge technology. Drawing on insults, the study’s objectives are to examine the verbal responses toward insults and the language features employed by the celebrities in the ‘Celebrity Read Mean Tweets’ segment on the Jimmy Kimmel show on Youtube. The data are verbal responses by 50 participants taken from the talkshow’s account. The analysis was carried out qualitatively by adopting the frameworks of Bond and Venus’ verbal responses accompanied by the gender language features of Lakoff and Coates. The results suggested that verbal responses were mainly employed to resist the insults. The strategies of resisting were conducted mostly via antinomies, correcting, and swearing. To signalize their acceptance, the speakers mostly appreciate the quality of the insult. Other purposes of the verbal responses were to ignore the insults which were done predominantly via digression. Subsequently, the highly employed language feature by the celebrities was lexical hedges/fillers and harsh words/swearing. Most of the features were used altogether by both genders, except for empty adjectives which were discovered from female responses. The results of this study can help explore strategies to tackle insults and future research related to verbal responses.